1996
DOI: 10.1007/s002329900044
|View full text |Cite
|
Sign up to set email alerts
|

Association of ClC-3 Channel with Cl − Transport by Human Nonpigmented Ciliary Epithelial Cells

Abstract: Electrophysiologic and volumetric evidence link the swelling-activated Cl- channels [gCl(Vol)] of nonpigmented ciliary epithelial (NPE) cells with the Cl(-)-channel/Cl(-)-channel regulator protein pICln. However, inhibitors (verapamil and dideoxyforskolin) of another Cl- channel/regulator (MDR1) have been found to inhibit the volume-activated transport response [the regulatory volume decrease (RVD)] of bovine NPE cells. We have addressed the possible molecular basis for the NPE Cl- channels by volumetric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 26 publications
4
46
0
Order By: Relevance
“…It was suggested that pICln, identified as a soluble cytosolic protein which forms specific complexes with actin and other cytosolic proteins, might be involved as a sensor or mediator in the change of cell volume, rearrangement of cytoskeletal components, and activation of chloride channels (Krapivinsky et al 1994(Krapivinsky et al , 1998. A model introduced by Coca-Prados et al (1996) integrates the function of ClC_3 and pICln. Their hypothesis was that ClC_3 provides a channel for chloride movement directly regulated by PKC, and pICln is a volume-sensitive regulator which controls the movement of chloride through the ClC_3 channel by a mechanism yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that pICln, identified as a soluble cytosolic protein which forms specific complexes with actin and other cytosolic proteins, might be involved as a sensor or mediator in the change of cell volume, rearrangement of cytoskeletal components, and activation of chloride channels (Krapivinsky et al 1994(Krapivinsky et al , 1998. A model introduced by Coca-Prados et al (1996) integrates the function of ClC_3 and pICln. Their hypothesis was that ClC_3 provides a channel for chloride movement directly regulated by PKC, and pICln is a volume-sensitive regulator which controls the movement of chloride through the ClC_3 channel by a mechanism yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that PICln, first cloned by Paulmichl, Li, Wickman, Ackerman, Peralata & Clapham (1992), is VSOAC (Strange et al 1996). In contrast, it has recently been suggested that ClC-3, first cloned from rat kidney by Kawasaki et al (1994), is the volume-activated Cl-channel in a human non-pigmented ciliary epithelial cell line (ODM-2 cells) (Coca-Prados, Sanchez-Torres, PetersonYantorno & Civan, 1996) and that this channel is regulated by PICln (Coca-Prados et al 1996). Further to this, but not necessarily in contradiction to it, Wu et al (1996) demonstrated that this volume-activated current was regulated by P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…A standard protocol was then used to evaluate the hypothesis that swelling might increase secretion by directly affecting distal steps in insulin granule exocytosis. Finally, as a first step toward ultimately establishing the molecular identity of I Cl,islet , reverse transcriptase (RT)-polymerase chain reaction (PCR) was used to determine whether mRNA for CLC-3 was present in HIT cells, because this Cl Ϫ channel isoform is a strong candidate for the outwardly rectifying swelling-activated Cl Ϫ channel of other tissues (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%